Does Pain in Individuals with Multiple Sclerosis Affect Employment? A Systematic Review and Meta-Analysis - Shahnaz Shahrbanian; Mohammad Auais; Pierre Duquette; Katie Anderson; Nancy E Mayo (Pain Research and Management)
BACKGROUND: Individuals with multiple sclerosis (MS) experience some of the highest unemployment rates among all groups of chronic illnesses. Pain has been found to be a common reason for sick leave or early retirement in healthy populations or other groups with chronic illness; however, there is little awareness regarding the effect of pain on the work status of individuals with MS.